2005
DOI: 10.1136/ard.2005.042135
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of asymptomatic cervical spine subluxation in patients with rheumatoid arthritis waiting for orthopaedic surgery

Abstract: Objective: To study the prevalence of cervical spine subluxation in patients with rheumatoid arthritis waiting for orthopaedic surgery, and symptoms that might be associated with the disorders. Methods: 194 patients with rheumatoid arthritis were referred for orthopaedic surgery at Jyväskylä Central Hospital, 154 (79%) of whom volunteered for the present study including clinical examination, laboratory tests, radiographs of the cervical spine, hands, and feet, and self report questionnaires. Definition of ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
75
2
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 22 publications
5
75
2
4
Order By: Relevance
“…27,38,44 The standard plain radiographic screening views include upright anteroposterior, lateral, and flexionextension views and an open-mouth view for odontoid visualization. 27,38,44 Bone alignment, quality, and deformities can easily be assessed with plain radiographs, but plain radiographs are limited in their ability to visualize bony erosions, the craniocervical and cervicothoracic junctions (due to superimposition of the cranial base structures and the glenohumeral joints), and soft tissue abnormalities such as pannus and spinal cord compression. If any cervical spine disease is suspected or confirmed with plain radiographs or the patient has any neurological symptom or important cervical pain, then CT and/or MRI examination of the cervical spine is indicated.…”
Section: Overview Of Imaging Modalities For Diagnosing Cervical Instamentioning
confidence: 99%
See 1 more Smart Citation
“…27,38,44 The standard plain radiographic screening views include upright anteroposterior, lateral, and flexionextension views and an open-mouth view for odontoid visualization. 27,38,44 Bone alignment, quality, and deformities can easily be assessed with plain radiographs, but plain radiographs are limited in their ability to visualize bony erosions, the craniocervical and cervicothoracic junctions (due to superimposition of the cranial base structures and the glenohumeral joints), and soft tissue abnormalities such as pannus and spinal cord compression. If any cervical spine disease is suspected or confirmed with plain radiographs or the patient has any neurological symptom or important cervical pain, then CT and/or MRI examination of the cervical spine is indicated.…”
Section: Overview Of Imaging Modalities For Diagnosing Cervical Instamentioning
confidence: 99%
“…Multilevel subluxations can produce a "staircase" deformity, associated with severe systemic RA. 18,22,27 In this paper, we review and discuss the limitations and benefits of each radiological method used to diagnose cervical instability, as well as the criteria used to classify the most common forms of cervical spine involvement in RA.…”
mentioning
confidence: 99%
“…However, the development of SAS is regulated by multiple factors, including not only the mechanical effect of fixed atlantoaxial angle and secondary subaxial kyphosis, but also disruption of the extensor muscles in addition to a strong effect due to a natural history of RA. Some authors have reported that the incidence of SAS in RA patients not surgically treated was 15-22 % [1,22,23] and of AAS was 18-61 % [1,22]. In patients who were surgically treated, a higher incidence of newly developed SAS and AAS after AA fusion using wiring systems or transarticular screws has been reported (32.7-39 % [9][10][11] and 100 %, respectively).…”
Section: Discussionmentioning
confidence: 96%
“…When the cervical spine is involved this risk is increased (Paus et al, 2008;Riise et al, 2001;Shen et al, 2004). In the RA population the estimates of the number of patients with cervical involvement varies from 12% (Naranjo et al, 2004) to 57% (Neva et al, 2006). Cervical spinal disorders should be diagnosed early and treated actively to prevent severe and potentially fatal complications (Neva et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In the RA population the estimates of the number of patients with cervical involvement varies from 12% (Naranjo et al, 2004) to 57% (Neva et al, 2006). Cervical spinal disorders should be diagnosed early and treated actively to prevent severe and potentially fatal complications (Neva et al, 2006). Early surgery corrects AS and prevents further instability (Grob et al, 1999;Hamilton et al, 2001;McRorie et al, 1996).…”
Section: Discussionmentioning
confidence: 99%